T-cell-derived TNF-α and a cluster of immunological parameters from plasma allow a separation between SARS-CoV-2 convalescent versus vaccinated elite athletes - Palmowski, Jana; Kohnhorst, Sarah; Bauer, Pascal; Puta, Christian; Haunhorst, Simon; Gebhardt, Kristina; Reichel, Thomas; Keller, Christian; Huber, Magdalena; Raifer, Hartmann; Krüger, Karsten (Frontiers in Physiology, 2023)
Guidelines for medical clearing after SARS-CoV-2 infection in elite athletes do not include T-cell immunity aspects despite its relevance in the course of COVID-19 disease. Therefore, we aimed to analyze T cell-related cytokines before and after in-vitro activation of CD4+ T cells. We sampled professional indoor sports athletes at medical clearing after SARS-CoV-2 infection obtaining clinical, fitness data, and serological data including CD4+ T cell cytokines. All data were analysed by principal component analysis and 2x2 repeated measures ANOVA. CD4+ T cells were sampled for cell culture activation with anti-CD3/anti-CD28 tetrameres. At medical clearing CD4+ T cell from convalescent athletes secreted increased levels of TNF-α 72 hours after in-vitro activation compared to vaccinated athletes. IL-18 levels in plasma were elevated and a cluster of parameters differentiated convalescent from vaccinated athletes by 13 parameters at the timepoint of medical clearing. All clinical data indicate infection is resolved, while increased TNF-α may reflect altered proportions of peripheral T-cells as a hangover of infection.